(untitled) (Heritage, 2022)
This paper deals with the teaching of English academic vocabulary in master’s degree academic studies. The aim of this paper is to examine the extent to which students can properly use English academic terms after various exercises applied within the English classes, as well as a correlation between the students’ prior knowledge of English and their ability to use English academic terms properly. In other words, the research also aimed to determine whether the usage of certain exercises could result in a greater share of properly used English academic terms. The respondents were students of the master’s degree academic studies of the study programme Agriculture of the Faculty of Agriculture, University of Belgrade. The results indicate that, in general, all students used English academic terms somewhat correctly, while the best results were achieved by those engaged in productive practice tasks, such as writing a paragraph, regardless of their English language proficiency. In addition, the analysis of variance ANOVA followed by a Post Hoc Tukey’s HSD test revealed a statistically significant difference between the results of the groups of the highest and the lowest English language proficiency. The findings show a statistical significance of the correlation between students’ prior knowledge and the incidence of correctly used academic terms, which can be explained by the tendency of the most proficient students to use learning strategies such as lexical inference. In addition, some hints on how to help students with lower English language proficiency to use new academic terms correctly to the same extent as students who are more proficient in English are provided. In conclusion, possible guidelines are given for teaching academic vocabulary to increase the share of properly used academic terms and possible starting points for future research.